EFFICIENCY ANALYSIS OF BUILDING PROCUREMENT AND MANAGEMENT PLAN USING THE LIFE CYCLE COSTING METHOD - Muhammad Simba Sembiring; Dedy Suryadi; Rahmawaty Arifiani (Jurnal Ekonomi, 2022)
Trisakti University, in planning the resources needed, including plans for the procurement of goods and services, needs to make analytical calculations regarding these procurements with a comprehensive tool. This study aims to simulate the process of planning the procurement of goods/services by also considering various procurement options for goods/services, especially the required building. The Life Cycle Cost (LCC) method is used to evaluate the costs that must be incurred in the Trisakti University procurement plan. From the simulation results for the procurement of a new 8-story building with a building area of 14,216 m2, it can be concluded that the most efficient procurement alternative is the procurement of a building with a budgeted value of IDR 152,063,123,498.